Program to Improve Letter Recognition Skills For Children With Learning Difficulties Using Montessori Reading Techniques - Janah, Rahmatul; Susetyo, Budi (Universitas Negeri Padang, 2024)
Children with learning difficulties experience obstacles in the learning process, one of which is in the process of learning to read. Based on observations in the field, there is a child with learning difficulties aged 8 years who does not recognize the letters of the alphabet. Beginning reading for children with learning difficulties should use methods that suit their needs. One of the reading methods that can be used in the beginning reading process is the Montessori reading method. For this reason, this research aims to develop a program to improve letter recognition skills for children with learning difficulties using Montessori reading techniques. This program is developed based on the child’s ability analyzed from the results of developmental assessments on cognitive and language aspects. This program is implemented by researchers accompanied by parents of children with learning difficulties so that parents can continue the program later. This research uses mixed methods so that to collect and analyze data using qualitative methods and quantitative methods. The type of this research is Single Subject Research (SSR). The results of this study indicate that the letter recognition program with Montessori techniques can improve the ability to recognize letters for children with learning difficulties.Keywords: Letter recognition, children with learning difficulties, montessori reading techniques